1984
DOI: 10.1172/jci111193
|View full text |Cite
|
Sign up to set email alerts
|

Arthritis induced in rats by cloned T lymphocytes responsive to mycobacteria but not to collagen type II.

Abstract: Abstract. We have been studying the pathogenesis of adjuvant arthritis in rats using a long-term cell line of T lymphocytes, the A2 line, which can induce polyarthritis and can also be used to vaccinate rats against adjuvant arthritis. Although line A2 was selected for its proliferative response to mycobacteria, it also responded to collagen type II. To elucidate its role of responsiveness to collagen type II and the relationship between arthritogenicity and vaccination, we cloned A2 and selected a subline A2b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
137
0

Year Published

1989
1989
2008
2008

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 281 publications
(142 citation statements)
references
References 17 publications
3
137
0
Order By: Relevance
“…These data, together with the finding that swelling in the contralateral paw was inhibited by anti VLA-1 mAb, suggest that treatment with HA31/8 antibody is able to delay the disease development. It is likely that the beneficial effect of the anti-VLA-1 mAb is linked to a reduced activation and, as a consequence, trafficking and proliferation of the T cells through the lymph node, which have been shown to be key features in this experimental model of arthritis (Cohen et al, 1985;Haskard, 1993;Holoshitz et al, 1984;Yednock and Rosen, 1989). Indeed, treatment with HA31/8 caused also a significant inhibition of the total cell count harvested by DLN.…”
Section: Discussionmentioning
confidence: 91%
“…These data, together with the finding that swelling in the contralateral paw was inhibited by anti VLA-1 mAb, suggest that treatment with HA31/8 antibody is able to delay the disease development. It is likely that the beneficial effect of the anti-VLA-1 mAb is linked to a reduced activation and, as a consequence, trafficking and proliferation of the T cells through the lymph node, which have been shown to be key features in this experimental model of arthritis (Cohen et al, 1985;Haskard, 1993;Holoshitz et al, 1984;Yednock and Rosen, 1989). Indeed, treatment with HA31/8 caused also a significant inhibition of the total cell count harvested by DLN.…”
Section: Discussionmentioning
confidence: 91%
“…Additional studies to reveal the MHC specificity/restriction, T cell specificity, and effector function have been hampered with a multitude of difficulties. Nevertheless, it has been reported that T cells specific for heat shock protein can transfer arthritis; the mechanism was believed to be due to cross-reactivity of the transferred T cells with various joint Ags (31). However, these studies have not been reproduced, and histological evidence showed no or possibly only very mild synovitis (32).…”
Section: Discussionmentioning
confidence: 99%
“…We now add another mechanism to the list of possibilities, namely the induction of a protective immune response to the autoimmune disease-inducing epitope (ADIE), SNP in the case of AA. Of course, SNP itself has not been shown to be arthritogenic, but a T cell clone (A2b) which responds in vitro to SNP is arthritogenic (Holoshitz et al, 1984;Cohen et al, 1985). So far the common opinion postulates the induction of tolerance to ADIE or suppression ofthe immune response to ADIE as ways of achieving prevention or therapy of autoimmune diseases.…”
Section: Discussionmentioning
confidence: 99%
“…A nonapeptide (Thr-Phe-Gly-Leu-Gln-Leu-Glu-Leu-Thr), representing amino acid sequence 180-188 ofthe 65-kD mycobacterial HSP, has been suggested to carry the critical epitope(s) for A A because of its ability to stimulate the arthritis-inducing T cell clone A2b as well as the arthritis-protective T cell clone A2c in vitro (Holoshitz, Matitiau & Cohen, 1984;Cohen et at., 1985;van Eden et al, 1988;, Based on these observations, it was suspected that immunization with the Correspondence: Dr X,-D, Yang, R-1056. 1,18, Ciba-Geigy, CH-4002 Basle, Switzerland, synthetic nonapeptide (SNP) would either activate an A2b-like T cell subset to induce arthritis or it would stimulate an A2c-like T cell subset resulting in a protective response against AA (van Eden era/,, 1988;Yang era/,, 1990), In a previous study, we have shown that administration of SNP suspended in mineral oil did not induce AA but was able to suppress AA partially in Lewis rats (Yang et al, 1989(Yang et al, , 1990.…”
Section: Introductionmentioning
confidence: 99%